2011
DOI: 10.1073/pnas.1016275108
|View full text |Cite
|
Sign up to set email alerts
|

Spine growth in the anterior cingulate cortex is necessary for the consolidation of contextual fear memory

Abstract: Remodeling of cortical connectivity is thought to allow initially hippocampus-dependent memories to be expressed independently of the hippocampus at remote time points. Consistent with this, consolidation of a contextual fear memory is associated with dendritic spine growth in neurons of the anterior cingulate cortex (aCC). To directly test whether such cortical structural remodeling is necessary for memory consolidation, we disrupted spine growth in the aCC at different times following contextual fear conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(147 citation statements)
references
References 43 publications
8
137
2
Order By: Relevance
“…Spine remodeling and growth has been shown to occur in superficial layers during remote memory formation in mice (Lesburguères et al 2011;Vetere et al 2011;Xie et al 2014), and contextual fear conditioning has been shown to determine a memory-related activation of sparse neurons in layer II of several cortices in mice, which lasts for 2 months (Xie et al 2014). Taken together, past and the present data support the view that superficial layers represent key sites for memory processes.…”
Section: Layer-specific Memory Evoked Activity In the Te2 Cortexsupporting
confidence: 77%
“…Spine remodeling and growth has been shown to occur in superficial layers during remote memory formation in mice (Lesburguères et al 2011;Vetere et al 2011;Xie et al 2014), and contextual fear conditioning has been shown to determine a memory-related activation of sparse neurons in layer II of several cortices in mice, which lasts for 2 months (Xie et al 2014). Taken together, past and the present data support the view that superficial layers represent key sites for memory processes.…”
Section: Layer-specific Memory Evoked Activity In the Te2 Cortexsupporting
confidence: 77%
“…These changes have no effect on learning but produce severe memory loss weeks later (Frankland et al 2001). Consistent with this finding, spine growth in the anterior cingulate and orbitofrontal cortex is necessary for remote memory formation (Lesburgueres et al 2011;Vetere et al 2011). Together, these studies indicate that the consolidation of recently formed memories depends on the ability of the neocortex to form new synaptic connections (Frankland and Bontempi 2005).…”
Section: Assumptions Of Smcsupporting
confidence: 70%
“…Such findings have led to the idea that the hippocampus serves a critical role in integrating information from a distributed cortical network representing various features of a memory, and that over time, the medial prefrontal cortex (including the ACC) gradually takes over this integrative role, allowing the memory to function independently of the hippocampus (Frankland and Bontempi, 2005). In support of this view, imaging studies have revealed sequential activity in area CA1 in the hippocampus and ACC for recent and remote time points after learning, respectively, in terms of immediate-early gene expression (Frankland et al, 2004), and dendritic spine growth (Vetere et al, 2011). This transition has been suggested to reflect systems consolidation, during which post-training hippocampal replay of episodic or detailed memory leads to memory trace reactivation in the cortex, promoting the development of a more schematic cortical representation (McClelland et al, 1995;Winocur et al, 2010).…”
Section: Introductionmentioning
confidence: 63%